Concept approximations based on rough sets and similarity measures - Saquer, Jamil; Deogun, Jitender S. (Zielona Góra: Uniwersytet Zielonogórski)
The formal concept analysis gives a mathematical definition of a formal concept. However, in many real-life applications, the problem under investigation cannot be described by formal concepts. Such concepts are called the non-definable concepts (Saquer and Deogun, 2000a).
Keywords: formal concept analysis; similarity measures; rough sets; concept approximation